2019
DOI: 10.5114/hpr.2019.85659
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between meaning in life and resilience in older adults: a cross-sectional study

Abstract: health psychology report • volume 7(2), 9 original article background Meaning in life has been considered necessary for the psychological well-being of older adults. The aim of this study was to investigate the relationship between meaning in life and resilience in the elderly in Kerman, Iran. participants and procedure In this cross-sectional study, 300 older adults (aged more than 60 years) were included using the multistage sampling method in Kerman in 2018. The Connor-Davidson Resilience Scale (CD-RISC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Besides, meaning and purpose of life in RSOA was found highly correlated with the CD-RISC-CN and RSA-CN. Our result is in line with previous study that indicated a significant and positive correlation between meaning and purpose of life and resilience among older adults (Mohseni, Iranpour, Naghibzadeh-Tahami, Kazazi, & Borhaninejad, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…Besides, meaning and purpose of life in RSOA was found highly correlated with the CD-RISC-CN and RSA-CN. Our result is in line with previous study that indicated a significant and positive correlation between meaning and purpose of life and resilience among older adults (Mohseni, Iranpour, Naghibzadeh-Tahami, Kazazi, & Borhaninejad, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Steger et al (2008) proposed that those professing a meaningful life exhibited fewer negative emotions and life problems, hence higher resilience. More specific examples demonstrate that these outcomes also cut across generations and cultures (Du et al, 2017;Mohseni et al, 2019).…”
Section: The Mediating Variables: Resilience and Optimismmentioning
confidence: 99%
“…At the same time, there is the "cult of youth and beautiful bodies" in society [4]. Because of that, women may exhibit behaviours such as dieting, becoming physically active, or undergoing plastic surgery [5]. Physical activity and maintaining appropriate body mass are factors that make it easier to get through this crisis and accept the changes [6,7].…”
mentioning
confidence: 99%